2016
DOI: 10.1515/forj-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Ozone phytotoxicity in the Western Carpathian Mountains in Slovakia

Abstract: In this work, the response of temperate coniferous forests to ozone air pollution (O 3 ) recommended for the protection of spruce forests were exceeded at all experimental plots from early July. Similarly, AOT40 index suggests vulnerability of mountain forests to O 3 pollution. AOT40 values increased with altitude and reached values varying from 6.2 ppm h in Stará Lesná (810 m a.s.l.) to 10.7 ppm h at Skalnaté Pleso close to the timber line (1,778 m a.s.l.). Concentration-based critical level (CLec) of 5,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In fact, the average POD1 value of Italy was 20.4 mmol m −2 with spikes up to 100 mmol m −2 . Such values are higher than values estimated at individual forest stands in central and Northern Europe (Tatra mountains 23 , 14–16 mmol m −2 ; Southern Sweden 24 , ~ 18 mmol m −2 ) and similar to values simulated for East-Asian forests (continental and (sub)tropical forests 20 , 20–105 mmol m −2 ). Also East Asia is known as a hot-spot of O 3 pollution 25 .…”
Section: Discussionsupporting
confidence: 51%
“…In fact, the average POD1 value of Italy was 20.4 mmol m −2 with spikes up to 100 mmol m −2 . Such values are higher than values estimated at individual forest stands in central and Northern Europe (Tatra mountains 23 , 14–16 mmol m −2 ; Southern Sweden 24 , ~ 18 mmol m −2 ) and similar to values simulated for East-Asian forests (continental and (sub)tropical forests 20 , 20–105 mmol m −2 ). Also East Asia is known as a hot-spot of O 3 pollution 25 .…”
Section: Discussionsupporting
confidence: 51%
“…A study by Bičárová et al ( 2016 ) implied that the seasonal dynamics of O 3 concentrations at high altitudes over Central Europe exhibited maxima: first in April and second in August, and usually, the second was higher than the first. Our research revealed that the same result may not be the case for lower situated localities, with the maximum average GLO values being 2015–2020 recorded in September.…”
Section: Discussionmentioning
confidence: 99%
“…Frequency and scales of the natural disturbances, as well as droughts, are expected to increase with climate changes (Svobodova et al, 2019). In the mountains of the Eastern Tatras (Western Carpathians, Slovakia) during the vegetation period of 2014, at the heights of 810 m to 1,778 m above the sea level, a high phytotoxic potential of О 3 was determined, which increased with height above the sea level and had negative effect on the increment of European spruce (Bicarova et al, 2016).…”
Section: Discussionmentioning
confidence: 99%